COMMUNITY-DRIVEN INNOVATION: COCONUT SHELL CHARCOAL AND STYROFOAM IN POROUS ASPHALT MIXTURES. INOVASI BERBASIS MASYARAKAT: ARANG TEMPURUNG KELAPA DAN STYROFOAM DALAM CAMPURAN ASPAL PORUS - Syammaun, Tamalkhani; Azzahra, Fatimah; Nasution, Emmi Suryani; Aksal, Ilham; Nurhilani, Siti (Universitas Muhammadiyah Aceh, 2023)
The Ingin Jaya District in Aceh Besar Regency has an area of 2,434 hectares. One of the villages in the Ingin Jaya District is Teubang Phui Village, located 11.5 km from the University of Muhammadiyah Aceh. In this village, there is one medium-sized small industry that will be a partner, namely Naturi Alam Semesta, which produces coconut shell charcoal. Coconut shell charcoal powder contains silica as a reinforcement for asphalt mixtures. Porous asphalt is an asphalt mixture with a uniform aggregate gradation, where the percentage of coarse aggregate is higher than fine aggregate. This gradation has large voids that weaken the interlocking of aggregates and make it easily detachable, resulting in a shorter service life compared to conventional asphalt mixtures. The stability of porous asphalt mixtures depends on the quality of asphalt as the binding material for aggregates, so high-quality modified asphalt is required for porous asphalt mixtures. One technology developed to improve the quality of asphalt as a binding material is modifying additional materials using residual or waste materials. Testing of test specimens includes the Marshall parameter, asphalt flow down, Cantabro loss, and permeability, with a total of 75 test specimens carried out in the Civil Engineering Laboratory of the University of Muhammadiyah Aceh. The urgent problem faced by the partner at this time is the lack of human resources and not having a charcoal crushing machine. The aim is to empower the surrounding community as partner human resources and introduce technology to the partner for the processing of coconut shell charcoal into powder that can be used as a filler, thereby increasing productivity and meeting market demand. The stages in implementing technology dissemination activities to partners and the community are identifying coconut production, coconut shell needs, technology for the crushing and mixing processes required. Keywords: Porous asphalt mixture; Coconut shell charcoal powder; Styrofoam.